Nek2 Is a Novel Regulator of B Cell Development and Immunological Response - Gu, Zhimin (Biomed Res Int, 2014)
The serine/threonine kinase Nek2 is commonly found upregulated in a wide variety of neoplasms including diffuse large B cell lymphoma and multiple myeloma. High expression of Nek2 is implicated in the induction of chromosomal instability, promotion of cell proliferation, and drug resistance in tumor cells as well as a marker for poor clinical outcomes. Despite its well recorded involvement in chromosomal instability and neoplastic growth, little is known about the involvement of Nek2 in B cell development. Here we report the development of a transgenic mouse line with conditional expression of Nek2 in the B cell lineage and the effects it has on the development of B cells. Interestingly, we found that the overexpression of Nek2 does not induce spontaneous tumor formation within the transgenic mice up to 24 months after induction. Instead, overexpression of Nek2 in the B cell lineage affects the development of B cells by increasing the proportion of immature B cells in the bone marrow and decreasing B-1 B cells in peritoneal cavity. Furthermore, Nek2 transgenic mice develop spontaneous germinal centers and exhibit an enhanced T cell dependent immune response. Altogether, our data demonstrates a novel role for Nek2 in regulating B cell development and the immune response.